ANALISIS PENGAKUAN PENDAPATAN PASIEN BPJS PADA RUMAH SAKIT UMUM DAERAH dr. H. L.M. BAHARUDDIN, M.Kes - Husin Husin; Nurwati Nurwati (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The objective of this study is to comprehend the process of revenue recognition for patients covered by BPJS. This research employs a quantitative descriptive methodology, utilising a case study conducted at the Regional General Hospital dr. H. L.M. Baharuddin, M.Kes. Data collection was performed through interviews and documentation. The acquired data was subsequently examined to ascertain the Hospital's method of revenue recognition for BPJS patients. The research findings indicate that at this particular location, revenue recognition is carried out using an accrual-based accounting system through the implementation of the INA-CBGs (Indonesia Case Base Groups) package application for BPJS patients. This technique is consistent with the guidelines outlined in the Statement of Financial Accounting Standards (PSAK) 72 regarding revenue generated from contracts with clients. The implementation of the accrual basis enables the Hospital to record income when health services are rendered to patients. The utilisation of the INA-CBGs package as a foundation for billing also aligns with the principles stated in PSAK 72, particularly in terms of quantifying the distribution of transaction charges. This conformity demonstrates that the Hospital being examined has implemented suitable accounting procedures that adhere to relevant standards.